Motivasi Konsumen terhadap Keputusan Pembelian Kopi Organik - Hariyanto, Adi; Noer, Irmayani; Kurniawan, Henry (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
This study aims to analyze the influence of consumer motivation on the purchase decision of organic coffee in Bandar Lampung. The focus is to determine the extent of intrinsic and extrinsic motivation's role in shaping consumer behavior. The research was conducted from January to March 2025 using a quantitative approach and survey method. A total of 100 respondents were selected through accidental sampling. Data were analyzed using the SEM-PLS method with SmartPLS 3.0 software. The results show that motivation has a significant direct effect on purchase decisions. This indicates that highly motivated consumers—whether due to health, environmental, or ethical reasons—tend to be more committed in buying organic coffee. These findings provide strategic implications for organic coffee businesses in developing value-based marketing strategies.